Multidimensional Self-Concept and Its Association with Problematic Use of Video Games in Spanish College Students - Manuel Castro-Sánchez; Mercedes Rojas-Jiménez; Félix Zurita-Ortega; Ramón Chacón-Cuberos (MDPI AG, 2019)
Background: At present, new technologies provide numerous benefits in their correct use, while the need arises to study the consumption of some technologies, in this case, videogames, due to the negative consequences that they can cause in those subjects who have not yet consolidated their personality due to their excessive use. The study aimed to determine and establish associations between the dimensions of self-concept and the problematic use of videogames and their gender differences. Methods: A total of 525 university students participated in this study, representing 44.7% of the male gender and 55.3% of the female gender, with an average age of M = 20.80 SD = 3.12 years old. The instruments used were the CESR and AF-5 questionnaires. Results: The results reveal the association (p ≤ 0.05) between the problematic use of videogames and the dimensions of self-concept, showing that students with severe or potential problems have lower levels of self-concept. In addition, it has been found that men have more problems associated with the use of video games than women. Men have a greater physical and emotional self-concept, while women have better social self-concept. Conclusions: This study highlights the inverse association between self-concept and problematic use of video games, a fact that shows the need to develop intervention programs aimed at improving self-concept and to reduce the problematic use of video games. Likewise, the levels of self-concept reveal that men have higher scores in the emotional and physical dimension, while women stand out in the social dimension.